2004
DOI: 10.1177/095440620421801108
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of heat transfer from a transonic jet impinging on skin for needle-free powdered drug and vaccine delivery

Abstract: In this paper, gas dynamics and temperature distribution of a transient impinging jet, typically used to deliver powdered drug or vaccines ballistically to the skin, have been numerically simulated. Calculations were performed with the unsteady compressible Navier-Stokes equations, solved using a modified implicit flux vector splitting (MIFVS) difference scheme with a modified k-e model. After validation against an experimental underexpanded jet-flow test cast, the code was applied to two biolistic configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The velocity of polymeric micro-particles of 15.5 mm diameter only reaches 330 m/s at 60 bar for the LGG system (Mitchell et al, 2003). Kis et al (2012) have concluded that the particle velocity reached about 700 m/s for CST and range from 200 to 800 m/s for converging-diverging nozzles (Quinlan et al, 2001;Kendall, 2002;Liu & Kendall, 2004b). Recently, Menezes et al (2012) have operated an advanced laser plasma jet to drive gold micro-particles of 1 mm diameter to achieve an average velocity of 1100 m/s within a distance of only 10 mm.…”
Section: Gas Pressure and Particle Velocitymentioning
confidence: 96%
“…The velocity of polymeric micro-particles of 15.5 mm diameter only reaches 330 m/s at 60 bar for the LGG system (Mitchell et al, 2003). Kis et al (2012) have concluded that the particle velocity reached about 700 m/s for CST and range from 200 to 800 m/s for converging-diverging nozzles (Quinlan et al, 2001;Kendall, 2002;Liu & Kendall, 2004b). Recently, Menezes et al (2012) have operated an advanced laser plasma jet to drive gold micro-particles of 1 mm diameter to achieve an average velocity of 1100 m/s within a distance of only 10 mm.…”
Section: Gas Pressure and Particle Velocitymentioning
confidence: 96%
“…5), was conceived and developed (Kendall 2002;Liu and Kendall 2004a;Hardy and Kendall 2005;Marrion et al 2005;Truong et al 2006;Liu et al 2007). The devices operate with the principle of delivering a payload of microparticles to the skin with a narrow range of velocities, by entraining the drug payload in a quasi-one-dimensional, steady supersonic flowfield.…”
Section: Engineering Of Hand-held Biolistic Devices For Clinical Usementioning
confidence: 97%
“…It has been demonstrated that the current implicit formulation is adequately efficient when applied to FVS methods, while maintaining a high level of robustness and accuracy [7][8][9]12]. Compared with conventional implicit methods, the MIFVS is a Jacobian spectral-radius scheme and a nonapproximate-factorization scheme.…”
Section: Spatial Discretisationmentioning
confidence: 99%
“…The semi-discrete delta expression for Eq. 1 also applicable to (2) of the low-Reynolds-number k-ε model, is derived as in [7,8] …”
Section: Implicit Formulationmentioning
confidence: 99%
See 1 more Smart Citation